2016 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2016
DOI: 10.1109/smc.2016.7844521
|View full text |Cite
|
Sign up to set email alerts
|

Towards human-robot interaction: A framing effect experiment

Abstract: Decision making is a critical issue for humans operating unmanned vehicles. However, it is well admitted that many cognitive biases affect human judgments, leading to suboptimal or irrational decisions. The framing effect is a typical cognitive bias causing people to react differently depending on the context, the probability of the outcomes and how the problem is presented (loss vs. gain). There is a need to better understand the effects of these biases in operational contexts to optimize human-robot interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Also, by comparing the results of different scenarios, the influence of emotional commitment on the subject's decisions is observed. These statistical effects, related with the emotional commitment, were also observed in our previous work (Souza et al, 2016), but for only 14 subjects. Interestingly, each curve presented in Figure 3 is strictly increasing function that satisfies f (0) = 0 and f (1) = 1, which is required by PT.…”
Section: Definition Of the Probability Weighting Functionw(•)supporting
confidence: 84%
“…Also, by comparing the results of different scenarios, the influence of emotional commitment on the subject's decisions is observed. These statistical effects, related with the emotional commitment, were also observed in our previous work (Souza et al, 2016), but for only 14 subjects. Interestingly, each curve presented in Figure 3 is strictly increasing function that satisfies f (0) = 0 and f (1) = 1, which is required by PT.…”
Section: Definition Of the Probability Weighting Functionw(•)supporting
confidence: 84%
“…Following this perspective, Dehais et al (2010Dehais et al ( , 2012, Imbert et al (2014) andSaint Lot et al (2020) have demonstrated that very brief (∼200 ms) and located information removal was an efficient mean to mitigate perseveration by forcing disengagement from non-relevant tasks. Souza et al (2016) demonstrated that digital nudging (see Weinmann et al, 2016) could be used to mitigate poor decision making and cognitive bias associated with perseveration. Imbert et al (2014) designed attention-grabbing stimuli grounded on vision research and demonstrated that yellow chevrons pulsing at a cycle of 1 Hz can re-orientate attention and mitigate inattentional blindness.…”
Section: Adaptation Of the User Interfacementioning
confidence: 99%
“…Stakeholders may frame certain aspects of a project in a positive or negative light to influence perspectives on that specific aspect. In HMT and Artificial Intelligence (AI), humans placed in human-AI teams may have their trust and decisions impacted by the framing effect [27,30,31]. Hindsight bias [28] may impact stakeholders as they tend to see past events as predictable at the time they occurred.…”
Section: General Stakeholder Biasesmentioning
confidence: 99%